2,2-Dimethyl-2,3-dihydro-1H-perimidine - Maloney, Sarah (International Union of Crystallography, 2013)
The title compound, C(13)H(14)N(2), was obtained from reaction of diaminonaphthalene with acetone. In both independent molecules in the asymmetric unit, the tricyclic perimidine consists of a planar (r.m.s. deviations = 0.0125 and 0.0181 Å) naphthalene ring system and an envelope conformation C(4)N(2) ringwith the NCN group hinged with respect to the naphthalene backbone by 36.9 (2) and 41.3 (2)° in the two independent molecules. The methyl substituents are arranged approximately axial and equatorial on the apical C atom. In the crystal, one of the N—H groups of one independent molecule is involved in classical N—H⋯N hydrogen bonding. Short intermolecular (C/N)—H⋯π(arene) interactions, near the short T-shaped limit, link molecules in the absence of strong acceptors.